Efectos de la violencia familiar en la calidad de vida de las mujeres calle Zela del distrito El Porvenir, 2021 - Ramos Hoyos, Andrea Melina (2022)
The present investigation was carried out with the purpose of explaining the way in which family violence by the couple affects the quality of life of women in Francisco de Zela street, El Porvenir-2021. From the development of the present investigation, it was possible to arrive at the following outcomes: The way in which family violence affects the quality of life of women on Francisco de Zela street in the Porvenir district is summarized that family violence destroys the victim's self-esteem and even generates thoughts of suicide. Likewise, it was possible to corroborate that the effects and consequences of the family violence of the women of Francisco de Zela street in the Porvenir district not only affects them as victims but also their closest relatives such as sons and daughters of the partner causing psychological damage, also running the risk of naturalizing acts of violence and transmitting them from generation to generation. Given the problem described above, after analyzing and interpreting the data obtained, the following is mainly recommended: The existing public and private institutions in the area that deal with cases of family violence must provide psychological care not only to direct victims, but also to their close environment such as their sons and daughters in order to prevent the intergenerational transmission of violence